2014
DOI: 10.1186/1748-5908-9-32
|View full text |Cite
|
Sign up to set email alerts
|

How collaborative are quality improvement collaboratives: a qualitative study in stroke care

Abstract: BackgroundQuality improvement collaboratives (QICs) continue to be widely used, yet evidence for their effectiveness is equivocal. We sought to explain what happened in Stroke 90:10, a QIC designed to improve stroke care in 24 hospitals in the North West of England. Our study drew in part on the literature on collective action and inter-organizational collaboration. This literature has been relatively neglected in evaluations of QICs, even though they are founded on principles of co-operation and sharing.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 54 publications
3
85
0
Order By: Relevance
“…A single-site study using a Six Sigma approach to improve door-to-needle times, however, has shown sustained improvements over time, suggesting that sustainability may also be more achievable in a single hospital setting rather than across a hospital system 24. As in other studies, our data confirm the smaller but significant and sustained effect of data feedback alone to improve performance, especially in sites that are organised and motivated to change and when external system mandates for improvement exist, although in a qualitative analysis of response to data sharing in collaboratives, not all participants find benchmarking of data to be a positive experience 25. Although more work to tease out the differential effects of various implementation strategies on specific types of indicators is needed, our finding that time and baseline performance were most consistently associated with early and sustained improvement suggest that these factors should be clearly documented and included when evaluating the effect of any new quality improvement programme.…”
Section: Discussionsupporting
confidence: 88%
“…A single-site study using a Six Sigma approach to improve door-to-needle times, however, has shown sustained improvements over time, suggesting that sustainability may also be more achievable in a single hospital setting rather than across a hospital system 24. As in other studies, our data confirm the smaller but significant and sustained effect of data feedback alone to improve performance, especially in sites that are organised and motivated to change and when external system mandates for improvement exist, although in a qualitative analysis of response to data sharing in collaboratives, not all participants find benchmarking of data to be a positive experience 25. Although more work to tease out the differential effects of various implementation strategies on specific types of indicators is needed, our finding that time and baseline performance were most consistently associated with early and sustained improvement suggest that these factors should be clearly documented and included when evaluating the effect of any new quality improvement programme.…”
Section: Discussionsupporting
confidence: 88%
“…First, LCs facilitate interactions directly between participants and faculty content experts during the in-person learning sessions, conference calls, and team consultations (Carter et al, 2014). Faculty content experts are a direct source of technical information about new practices and implementation strategies and thus, are critical for promoting successful implementation.…”
Section: Learning Collaboratives As Network Building Implementation Smentioning
confidence: 99%
“…In other studies, opportunities for participants to interact and learn from expert faculty and other participants were perceived as the most helpful LC features (Carter, Ozieranski, McNicol, Power, & Dixon-Woods, 2014; Ebert, Amaya-Jackson, Markiewicz, Kisiel, & Fairbank, 2011; Nembhard, 2009), and the inter-organizational contacts, specifically, were significantly associated with improved team performance (Nembhard, 2011). However, the overall evidence of LCs’ effectiveness in improving care quality and implementing treatment innovations is mixed (Schouten, Hulscher, van Everdingen, Huijsman, & Grol, 2008), and little is known about whether LCs “rewire” social networks in a way that supports implementation.…”
mentioning
confidence: 92%
“…In addition to the ecosystem, the behaviours and motivations of teams entering improvement collaboratives appear to be as important as the environmental context. For example, in Stroke 90:10 negative and positive behaviours from teams were present in equal measure with observations of social loafing and freeriding 4 5. These behaviours go some way to explaining the likelihood of a team to ‘benefit’ from the improvement intervention as designed and currently are best investigated through qualitative research methods such as ethnography and semistructured interview.…”
mentioning
confidence: 99%